Value-chain analysis of freshwater apple snail (Pila globosa) used for on-farm feeds in the freshwater prawn farming sector in Bangladesh - Nahid, SAA; Henriksson, PJG; Wahab, MA (International Journal of Agricultural Research, Innovation and Technology, 2014)
Growth of the freshwater prawn (Macrobrachium rosenbergii) sector in Bangladesh since 1970s has been supported by natural availability of freshwater apple snail (Pila globosa), used for on-farm prawn feeds. The present study identified the current configuration of the value-chain benefits and constraints of freshwater apple snail in south-western Bangladesh in August 2011, based upon Rapid Market Appraisal (RMA) approach. The site of snail collection was Chanda Beel in Gopalganj district, while trading, processing and final consumption was represented by Rayer Mahal Bazar in Khulna district. There were seven different nodes recognized throughout the value chain. Snail marketing was identified as a seasonal business and took place during June to November each year. Between 1995 and 2011 the price of whole snail, meat and shell has increased by 800%, 325% and 315%, respectively. The abundance of snail had been reduced and its demand has increased due to the expansion of the prawn farming industry. Prawn farmers preferred snail meat due to its low cost (US 0.21 kg-1) as a source of protein compared to commercial prawn feed (US 0.41 kg-1). Snail harvesting and processing were considered as additional livelihood options for the poor, where 60% of the labour involved in snail harvesting were women, and 95% the de-shelling workforce. Induced breeding in captivity and sustainable management in nature as well as development of commercial production of apple snails might reduce the pressure on ecosystems and positively contributed to the continued expansion of freshwater prawn farming in Bangladesh. DOI: http://dx.doi.org/10.3329/ijarit.v3i2.17840 Int. J. Agril. Res. Innov. & Tech. 3 (2): 22-30, December, 2013